ASAS-CSAS ANNUAL MEETING SYMPOSIUM ON WATER USE EFFICIENCY AT THE FORAGE-ANIMAL INTERFACE: Life cycle assessment of forage-based livestock production systems. (21st January 2019) - Philipp, Dirk; Putman, Ben; Thoma, Greg
Abstract: Livestock production is increasingly subjected to environmental and economic challenges related to water quantities being utilized, expressed as green (evapotranspiration from rainwater), blue (surface and groundwater), or gray (waste) water footprints at each stage of the product life cycle. Published data indicated that the largest share of water being used for producing beef in the United States can be traced back to growing forage and feed (>90%), whereby the green water footprint was substantially greater (12, 933 liters of water per kg of product) than the blue water footprint, as only a small amount of pasture- and cropland is irrigated (525 L/kg). Based on prevailing quantification methods, feed conversion ratios, and grazing land required, water footprints for beef produced through grazing alone can be relatively high. Green water footprints can easily reach more than 19, 000 L/kg for beef from grazing compared with a maximum of 1, 731 L/kg for chicken under a typical scenario. However, much of the existing grazing land cannot or should not be converted to cropland for various ecological reasons, and large water footprints would remain for the vegetation even if cattle were removed. Life cycle assessments (LCA ) were historically developed to provide a framework for evaluation of the full life cycle of a product or service and to ultimately model environmental impacts through life cycle impact assessment methods. Life cycle assessments grew more refined during past years and efforts are being made to reflect the environmental and economic consequences of different livestock and crop production systems more accurately than in the past. Typical beef production systems on natural and naturalized grasslands in North America generate environmental, economic, and societal benefits that should be reflected in future LCA, farm policies, and regulations. To increase the water use efficiency of each segment of the beef supply chain and thereby to reduce water footprints, grazing systems and methods as well as external inputs should be further optimized and integrated toward enhanced ecosystem services, thereby lowering the overall environmental impact of livestock production.